2021
DOI: 10.1186/s40168-021-01103-z
|View full text |Cite
|
Sign up to set email alerts
|

The microbial metabolite p-Cresol induces autistic-like behaviors in mice by remodeling the gut microbiota

Abstract: Background Autism spectrum disorders (ASD) are associated with dysregulation of the microbiota-gut-brain axis, changes in microbiota composition as well as in the fecal, serum, and urine levels of microbial metabolites. Yet a causal relationship between dysregulation of the microbiota-gut-brain axis and ASD remains to be demonstrated. Here, we hypothesized that the microbial metabolite p-Cresol, which is more abundant in ASD patients compared to neurotypical individuals, could induce ASD-like b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 99 publications
2
69
1
Order By: Relevance
“…Thus, a possible link between gut microbiota and ASD has been proposed. Moreover, changes in the composition of the gut microbiota and metabolites have been found in both ASD patients and animal models ( Kushak et al, 2016 ; Bermudez-Martin et al, 2021 ). Meanwhile, toxins produced by abnormal gut microbiota can increase intestinal permeability and aggravate ASD symptoms, for example, Fusobacterium produces some nerve factors and exerts systemic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a possible link between gut microbiota and ASD has been proposed. Moreover, changes in the composition of the gut microbiota and metabolites have been found in both ASD patients and animal models ( Kushak et al, 2016 ; Bermudez-Martin et al, 2021 ). Meanwhile, toxins produced by abnormal gut microbiota can increase intestinal permeability and aggravate ASD symptoms, for example, Fusobacterium produces some nerve factors and exerts systemic effects.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of p-Cresol on behavior was associated with the gut microbial composition, as microbial transplantation from p-Cresol-treated mice to control mice can stimulate behavioral defects. However, microbial transplantation from normal mice to p-Cresol-treated mice was found to restore normal social behaviors [58]. This report suggested that a microbial metabolite such as p-Cresol could provoke ASD-like behavior in mice.…”
Section: The Metabolic Pathwaymentioning
confidence: 81%
“…C. difficile can induce the p-hydroxyphenylacetate (p-HPA) enzyme and therefore stimulate the fermentation of tyrosine for the production of p-Cresol [97]. Notably, mice given p-Cresol in drinking water for four weeks exhibited an altered gut microbiota composition and social-behavioral defects [58]. The p-Cresol intervention also decreases the excitability of dopamine neurons in the ventral tegmental area (VTA) of these mice, a circuit implicated in the social reward system [98].…”
Section: The Metabolic Pathwaymentioning
confidence: 99%
“…Of interest is the recent finding that microbiota transfer therapy lowered enhanced fecal p CS levels in ASD similar to those of the typically developing controls ( Kang et al, 2020 ). Furthermore, mice chronically exposed to p -cresol in the drinking water demonstrated an ASD-like behavioral phenotype which was shown to be dependent on p -cresol-induced changes in the intestinal microbiota composition ( Bermudez-Martin et al, 2021 ). This highlights p -cresol and p CS as intriguing ASD-associated molecules with possible implications in the microbiota–gut–brain axis in ASD.…”
Section: Autism Spectrum Disorder-associated Bacterial Metabolites P -Cresyl Sulfate and 4-ethylphenyl Sulfatementioning
confidence: 99%